Pentingnya Memperkokoh Identitas Nasional Sebagai Pilar Negara: (Studi Kasus UINSU Jl. William Iskandar Ps. V, Medan Estate, Kec. Percut Sei Tuan, Kabupaten Deli Serdang) - Ali, Cindi Aulia; Efrida, Efrida; Khairunissa, Ica; Siregar, Nazwa Nadira; Afsari, Nova; Alzazira, Rara Aulia (CV. Pusdikra Mitra Jaya, 2024)
This research is motivated to find out the importance of strengthening national identity as a pillar of the country. The meaning of national identity itself is the identity or characteristics of a country that can distinguish it from other countries. The purpose of this study is to make readers aware that our country's national identity is very important. The method used in this study is a qualitative method with a technique of interviewing collaboration between the community and students. In conclusion, based on the results of observations from a viewpoint related to the Importance of Strengthening National Identity as a Pillar of the State, the public and students will understand that it is very important to know the national identity of our country. The community and students can apply it in education, family and in daily life.